Інтерлінація функцій двох змінних з використанням фундаментальних сплайнів - Литвин, О.М.; Кулик, С.І. (Видавничий дім "Академперіодика" НАН України, 2008)
The problem of construction of the spline-interlineation operators for functions of two variables is investigated. The problem of construction of the blending approximation operators for functions of two variables with the use of the local spline approximation operators for every variable is also studied. In the construction, the fundamental splines are used.